Spatial distribution and architecture of acromyrmex landolti forel (Hymenoptera, Formicidae) nests in pastures of Southwestern Bahia, Brazil - Silva, Magali Ribeiro da [UNESP]; Castellani, M. A.; Moreira, A. A.; D'Esquivel, M.; Forti, Luiz Carlos [UNESP]; Lacau, S. (Universidade Estadual de Feira de Santana, 2013)
Ants of the genera Atta and Acromyrmex (Myrmicinae: Attini) are in general pests for agricultural and pasture areas. In southwestern Bahia pastures, in Brazil, Acromyrmex landolti Forel occurs at intermediate densities of 260 nests ha-1. In spite of its economic importance, there is not enough research on the bioecological aspects of such species. This paper aims to study the spatial distribution and the architectural pattern of A. landolti nests, as well as to establish the foundations for the improvement of strategies for controlling the pest. The research was carried out during the period of June 2011 and May 2012, in an area of pastures measuring 2.7 ha, in Itapetinga, in Bahia. Twenty five nests were selected. The external mound area, height of the tower, distance between the tower and the external mound area, as well as the tower diameter were all registered. In order to describe the internal architecture, the same nests were completely excavated and five were molded in cement. The spatial distribution of the nests is of aggregated type. The towers height is 2.1 cm and the mean diameter is 1.2 cm. The amount of loose soil is of about 8.0 cm from the tower, with an mean area of 472.9±cm2 and mean volume of 1.4 ± 0.9 l. The depth of the nests varies between 7.0 and 78.0 cm, with an mean of 33.2±21.29 cm. The nests have, in mean, 4.4±2.0 chambers, being two nests with just one chamber (8%) and another nest (4%) with 11 chambers. The highest frequency of chambers (73.6%) occurs in the first 5-10 cm depth. The closest chambers have tunnels of 0.5 cm in length, and 23% of the tunnels measure 1.0 cm in length, with up to 44.7% of the tunnels measuring up to 30 cm. The mean dimensions of the chambers are: width: 6.2 cm; height: 5.1 cm; and length: 5.7 cm. The majority of the chambers are located near the entrance holes.
Keywords: Chambers; Channels; Depth; Negative binomial